Pendidikan Amar Ma’ruf Nahi Munkar - Rohimin Al ‘ Asror; Muhammad Hafidz Khusnadin; Ahmad Zumaro; Ilma Maulana Ahmad (Syntax Corporation Indonesia, 2025)
Education contributes greatly to the progress of a nation and is a mirror of the personality of society. Amar ma'ruf nahi munkar is one of the principles in Islamic teachings which means inviting to goodness and preventing evil. This command applies to all Muslims individually or in groups and is one of the main references in spreading the mission and da'wah of Islam to achieve prosperity. Amar ma'ruf nahi munkar education is important to foster a sense of concern for social conditions. The research method used in this research is qualitative with a normative approach. This article is a library research by searching for data through literature review, which is a series of activities related to the methods used in collecting library data. The literature review is conducted by collecting, evaluating, analyzing, and interpreting information contained in literature or written sources relevant to a particular research topic. Amar ma'ruf nahi munkar education has an important contribution to creating social stability. This education is a method to increase public awareness of the importance of good and prevent bad, this education has the potential to reduce criminal acts and deviant behavior.